AWS powered cloud research environment PaaS - Pedroso, Diego Frazatto; Pulcinelli, Lucas Eduardo Gulka; Aisawa, Wiliam Akihiro Alves; Bruschi, Sarita Mazzini (Anais da Escola Regional de Alto Desempenho de São Paulo (ERAD-SP); 2024: Anais da XV Escola Regional de Alto Desempenho de São Paulo, 2024)
Cloud computing has transformed organizational IT resource management. Among the prominent cloud service models, Infrastructure as a Service and Platform as a Service provided by Amazon Web Services stand out as integral components of modern cloud computing ecosystems. We’ve employed open-source tools to create a configurable infrastructure pipeline using Kubernetes to achieve high availability and consistency for research projects. Our platform integrates modern open-source stacks in order to reduce delivery time and complexity and increase observability, leveraging tools such as IaC and load testing frameworks. These practices blend academic and industry principles for comprehensive deployment and management of cloud-based applications.